North America. - Gellatly, J. (W. & R. Chambers, 1836)
Map shows Russian America [Alaska], Greenland, separate Texas, northern border of Mexico with Oregon Territory, northwestern borders of U.S. approximates 49th degree line of latitude, Central States [Central America] with separate Belize; areas of Native American habitation, major cities, and major physical features. Relief shown by hachures and spot heights. Scale [ca. 1:34,000,000].